Proceedings of the 2014 ACM International Joint Conference on Pervasive and Ubiquitous Computing: Adjunct Publication 2014
DOI: 10.1145/2638728.2638800
|View full text |Cite
|
Sign up to set email alerts
|

Motivational affordances and personality types in personal informatics

Abstract: Personal informatics applications have been gaining momentum with the introduction of implicit data collection and alert mechanisms on smart phones. A need for customized design of these applications is emerging and studies on tailoring UI design based on the personality traits of users are well established. This poster investigates how various affordances in gamified personal informatics applications affect motivation levels to track and achieve goals for users with different personality types. We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…the Big Five Inventory [35]) and player styles (e.g. BrainHex [71,72], Hexad [98]) play a significant role [10,56,74]. Many studies have investigated user typologies and their associated scales to predict preferences for different gamification elements [3,38,46,95].…”
Section: Introductionmentioning
confidence: 99%
“…the Big Five Inventory [35]) and player styles (e.g. BrainHex [71,72], Hexad [98]) play a significant role [10,56,74]. Many studies have investigated user typologies and their associated scales to predict preferences for different gamification elements [3,38,46,95].…”
Section: Introductionmentioning
confidence: 99%
“…by ascribing meanings to them), instead of pushing ourselves toward modalities of analysis closer to how machines "think". Moreover, providing diversified tools depending on the user's level of expertise can overcome the one-sizefits-all approach that has been strongly criticized even in the gamification domain [45,24]. This would balance the level of "challenge" in managing PI data on the basis of the individual's competence, turning this practice in a sort of an engaging game, whereby the "hardest" sense-making tasks would be accomplished by the more expert users by using sophisticated tools, and the inexperienced ones would be guided step-by-step by the system.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [100] reviewed how gamification can be utilized in conjunction with wearable devices for activity tracking, whereas Morschheuser et al [58] showed that gamification has a positive effect on the motivation to use PI applications. Leaderboards [101], points [8], and competitive dynamics [11] have been experimented to increase users' engagement with PI tools, also taking into account personality types [45] and developing tailor-made games directly connected with personal data [60].…”
Section: Related Workmentioning
confidence: 99%
“…Since the introduction of theories focusing on motivational affordances, motivational affordances in general and certain affordances, in particular, have been found to correlate with different learning types (Engedal 2015) and personality types (Karanam et al 2014): Some people react differently to the same affordances. This stresses the importance of gaining information about potential users before a system is implemented.…”
Section: Motivational Affordancesmentioning
confidence: 99%